SYIAH ZAIDIYAH: KONSEP IMAMAH DAN AJARAN-AJARAN LAINNYA - P. Omolu, Aminun (Institut Agama Islam Negeri (IAIN) Palu, 2012)
Abstract: One of the Shia sect is still growing up now is Shia Zaidiyah. Shiism Shia Zaidiyah is attributed to Zayd ibn Ali Zainal Abidin, the fifth priest in the hierarchy Zaidiyah Imamat. Zaidiyah Shiites tend to be moderate in the face of dilemmas caliphate of Ali ibn Abi Talib and the three caliphs before assessing his ¬, as priests and priests mafdhul Afdhal. The concept of Imamat and theology tends rational, while the other teachings of his ¬ Ahlussunnah generally synonymous with teaching. Zaidiyah Shiism has evolved since the third century AH in the Middle East and surrounding. Kata Kunci: Syiah Zaidiyaih, sekte Islam, konsep imamah.